2021
DOI: 10.1002/ps.6411
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal fluazaindolizine doses inhibit development of the cyst nematode Heterodera schachtii during sedentary parasitism

Abstract: BACKGROUND: Fluazaindolizine is a new compound for the control of plant-parasitic nematodes (PPNs) with an unknown and novel mode-of-action. This compound is very effective against important PPNs. However, investigations elucidating the impact of sublethal fluazaindolizine doses on early nematode virulence and plant-nematode interaction parameters are lacking. RESULTS:The effect of direct exposure of Heterodera schachtii juveniles to 50 ppm fluazaindolizine was negligible. Infection assays revealed a 57% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Further evidence is given by our in silico modeling studies showing that the amino acid difference is not located directly at the fluopyram binding pocket but could lead to steric reorganization of SDHC and thus indirectly interfere with ligand binding. Besides this, morphological characteristics like cuticle thickness, permeability and turnover rate of cyst and root-knot nematode J2 may play a role as well as discussed earlier to explain differences in sensitivity of these PPN towards fluazaindolizine 15 . Interestingly, we observed that C. elegans unlike M. incognita is able to recover from fluopyram treatment indicating that other so far not identified amino acids in the target might be important for ligand interaction and proper target function.…”
Section: Discussionmentioning
confidence: 84%
“…Further evidence is given by our in silico modeling studies showing that the amino acid difference is not located directly at the fluopyram binding pocket but could lead to steric reorganization of SDHC and thus indirectly interfere with ligand binding. Besides this, morphological characteristics like cuticle thickness, permeability and turnover rate of cyst and root-knot nematode J2 may play a role as well as discussed earlier to explain differences in sensitivity of these PPN towards fluazaindolizine 15 . Interestingly, we observed that C. elegans unlike M. incognita is able to recover from fluopyram treatment indicating that other so far not identified amino acids in the target might be important for ligand interaction and proper target function.…”
Section: Discussionmentioning
confidence: 84%
“…For the transfer, the plants were separated and two well- and similarly developed plants were transferred onto a new plate filled with about 16 ml RL-supplemented Knop agar or standard Knop agar as control. After two days of adaption, per plant 60-70 freshly hatched H. schachtii J2s [50] were inoculated in two drops along each primary root. Infection evaluation started 12 days post inoculation (DPI) by counting female and male nematodes under Stereo Microscope (Leica, Germany), followed by female size measurement 14 and 28 DPI using the LAS software (Leica Microsystems), and eventually female collection 35 DPI to invasively count the eggs and juveniles.…”
Section: Methodsmentioning
confidence: 99%
“…A transparent flat bottom 96-well cell culture plate was prepared by filling a minimum of four wells per variant and time point with 100 µl dRLs (188.75, 377.5, 755, and 1510 ppm) or double distilled water as control further containing about 50 J2s prepared following Matera et al [50]. Incubation was performed at room temperature and mortality was evaluated every 24 hours for four days using 10 µl of 5M sodium hydroxide (NaOH) per well with four technical replicates per time point and treatment.…”
Section: Nematode Mortality Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in two plants of each genotype growing on each plate. Ten‐day‐old plants were inoculated along the primary root with 60–70 freshly hatched H. schachtii J2s each (Matera et al ., 2021). The number of female and male nematodes was evaluated 12 days after inoculation using a Stereo Microscope (Leica, Germany), and mean values of nematode numbers were noted for the two plants on one plate.…”
Section: Methodsmentioning
confidence: 99%